Favipiravir does not appear to be a major teratogen: case series from Türki̇ye - KAŞKAL, MERT (My University, 2023)
Introduction: Favipiravir has gained attention during the Coronavirus Disease-2019 pandemic due to its potential antiviral effect against Severe Acute Respiratory Syndrome Coronavirus-2. Favipiravir has been identified as a teratogen in animal studies, but there is limited human data. We aimed to evaluate the pregnancy outcomes of women exposed to favipiravir during the pandemic. Material and Methods: Pregnant women who were exposed to favipiravir and applied to Marmara University School of Medicine Medical Pharmacology Outpatient Clinic Teratology Information Service between December 2020-September 2021 are included in the study. The demographic information, medical and obstetric histories of patients were acquired during admission, the outcomes of the pregnancies and the characteristics of the infants were gathered by regular phone calls. The infants whose parents consented were evaluated by a pediatrician for general well-being and congenital anomalies. Results: 22 pregnant women were included in this study. 81.8% received the recommended favipiravir dose (8000 mg in 5 days), in the first trimester. Two patients were lost to follow-up, there was one elective termination and 19 live births. Congenital anomalies were found in 2 infants, one of whom had 9q34 duplication syndrome. Except for these, all newborns examined by the pediatrician were healthy. Discussion: Within a limited case series, a subset of the infants exposed to favipiravir prenatally were followed up to 1 year of age. Two infants exhibited congenital malformations that cannot be directly linked to favipiravir due to confounding variables. Considering the limited data published, favipiravir does not appear to be a major teratogen.
Keywords: favipiravir; pregnancy; Covid-19; teratogen; congenital anomaly